Low catestatin as a risk factor for cardiovascular disease – assessment in patients with adrenal incidentalomas - Zalewska, Ewa; Kmieć, Piotr; Sobolewski, Jakub; Koprowski, Andrzej; Sworczak, Krzysztof (Frontiers in Endocrinology, 2023)
Abstract Background: Catestatin (Cts) is a peptide derived from proteolytic cleavage of chromogranin A, which exhibits cardioprotective and anti-inflammatory properties. Cts has been proposed as a potential biomarker for cardiovascular (CV) disease. Objectives: examining Cts in patients with incidentally discovered adrenocortical adenomas (AI), and its associations with CV risk factors and blood pressure (BP). Materials and Methods: In this cross-sectional study, 64 AI patients without overt CV disease other than primary hypertension were recruited along with 24 age-, sex-, and body-mass-index (BMI)-matched controls with normal adrenal morphology. Laboratory, 24-h ambulatory BP monitoring, echocardiography, and common carotid artery sonography examinations were performed. Results: Unadjusted Cts was higher in AI patients (median 6.5, interquartile range: 4.9-37 ng/ml) versus controls (4.5 (3.5 – 28)), p=0.048, however, the difference was insignificant after adjusting for confounding variables. Cts was lower in subjects with metabolic syndrome than in those without it (5.2 vs. 25.7 (5.8-115) (3.9- 6.9) ng/ml, p<0.01), and in men compared to women (4.9 (4-7.4) ng/ml vs. 7 (4.8-100), p=0.015). AI patients in the lower half of Cts levels compared to those in the upper had a higher prevalence of hypertension (OR 0.15, 95% CI: 0.041-0.5, p<0.001) and metabolic syndrome (OR 0.15, 95% CI 0.041-0.5, p<0.001). In AI patients Cts correlated positively with high-density lipoprotein cholesterol (Spearman’s r=0.31), negatively with BMI (r=-0.31), and 10-year atherosclerotic CV disease risk (r=-0.42). Conclusions: Our data indicate associations between CV risk factors and Cts. More clinical research is needed to apply serum Cts as a biomarker.